2015
DOI: 10.1097/inf.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Epidemiology of Children With Acute Otitis Media and Spontaneous Otorrhea in Suzhou, China

Abstract: S. pneumoniae was a leading cause for AOM in children in Suzhou, China. Antibiotics resistance rates of S. pneumoniae were high and mainly due to the spread of CC271 clonal complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…Another Russian study found that the rate of unjustified outpatient antibiotic prescriptions in children with respiratory infections was estimated at 40% 27. In PCV-unimmunised Chinese children with pneumococcal AOM, a significant proportion of clones were also resistant to antibiotics 28. In India, otolaryngologists reported that they treated 98% of AOM episodes with antibiotics, and amoxicillin/clavulanic acid was the first-line therapy 29.…”
Section: Discussionmentioning
confidence: 99%
“…Another Russian study found that the rate of unjustified outpatient antibiotic prescriptions in children with respiratory infections was estimated at 40% 27. In PCV-unimmunised Chinese children with pneumococcal AOM, a significant proportion of clones were also resistant to antibiotics 28. In India, otolaryngologists reported that they treated 98% of AOM episodes with antibiotics, and amoxicillin/clavulanic acid was the first-line therapy 29.…”
Section: Discussionmentioning
confidence: 99%
“…The strains of nonsurvivors in this study were multi-drug resistant. Domestic and foreign reports also showed that S. pneumoniae was generally multi-drug resistant, and the resistance to penicillin and cephalosporins increased [ 6 , 26 , 27 ]. Compared with drug sensitivity analysis in the present study, a better consistency rate was achieved if the choice of antibiotics strictly abided by China’s “Guidelines for the Management of Community Communicable Pneumonia (2013 Revision)”.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Pseudomoans aeruginosa (22.4%; 62) was isolated maximum, followed by 19 . In the current study, 31 (11.2%) Streptococcus pneumoniae were isolated.…”
Section: Discussionmentioning
confidence: 99%